2016
DOI: 10.4018/jgim.2016070103
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Software Development Practices among Small Firms in Developing Countries

Abstract: For software development firms to be competitive they must assure the quality of the software product. This has led many firms to adopt software process improvement (SPI) programs such as the capability maturity model integration (CMMI). However, for small software firms, especially those in developing countries with limited resources, these programs are often too cumbersome and costly to implement. To address this issue, this paper proposes a simplified SPI model for small firms (SPM-S) comprised of 10 key so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The indicators variables for the 'Process maturity' construct were taken from a study conducted by Chevers, Moore, Duggan & Mills (2008) in which they identified ten CMMI levels 2 and 3 process areas (which will be called 'CMMI practices') that were considered applicable for a simplified process improvement framework. These practices included risk management, technical solution, organization training, requirement management merged with requirement development, integrated project management, project planning, organization process definition, organization process focus, project monitoring and control and finally verification merged with validation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The indicators variables for the 'Process maturity' construct were taken from a study conducted by Chevers, Moore, Duggan & Mills (2008) in which they identified ten CMMI levels 2 and 3 process areas (which will be called 'CMMI practices') that were considered applicable for a simplified process improvement framework. These practices included risk management, technical solution, organization training, requirement management merged with requirement development, integrated project management, project planning, organization process definition, organization process focus, project monitoring and control and finally verification merged with validation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, one fundamental change was the inclusion of the ten indicator variables for the process maturity construct which were taken from the top ranked practices in a study by (Chevers et al, 2008) involving 30 IS professionals in four focus group sessions. In these focus group sessions, participants were presented with the eighteen (18) established CMMI levels 2 and 3 process areas (which are called practices in this study).…”
Section: Model Developmentmentioning
confidence: 99%
“…Combining advanced classification rules mining with classifiers provides a new type of association classifiers. They will discuss that this advanced association classifiers, which have been proposed in recent years, are more accurate than traditional classifiers [30][31][32]. Stork et al [14] investigated the use of decision tree to diagnose the heart disease of patients.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The IoTs have invented a set of technologies that invoke a wide range of tools, devices, and objects which call for interaction and interconnection with the use of network technologies [6][7][8]. There are numerous applications based on the IoTs [9,10], including the healthcare system, the production systems [11] and the bus system [12]. Healthcare systems from a set of connected devices are used for creating an Internet Network.…”
Section: Introductionmentioning
confidence: 99%